The RELATIONSHIP OF MACRONUTRIENT INTAKE WITH NUTRITIONAL STATUS PREGNANT WOMEN IN THE WORKING AREA OF THE PUSKESMAS PASAR SUNDAY DISTRICT - Tri Ade Tiana Dewi; Putri Azzahroh; Vivi Silawati (International Health Sciences Journal, 2024)
Background: Increasing the nutritional status of the community is one of the development priorities in the 2015-2019 National Medium Term Development Plan (RPJMN) document. Based on the results of the 2018 Basic Health Research (Riskesdas), most of the main targets are estimated to not be able to achieve the target. The problem of malnutrition in women of childbearing age is seen in the high rate of Chronic Energy Deficiency (CED). In non-pregnant women, the CED rate was 14.4% and 17.3% in pregnant women. Methodology: Research carried out using an observational approach taken at the same time aims to study the relationship between the independent variable, namely macronutrient intake and the dependent variable LILA of pregnant women by conducting a 3 × 24 hour food recall of pregnant women's food intake. The sample in this study was 92 people, the sampling technique used the Fisher exact technique. The statistical test used the person correlation test. Research Results: The results of research conducted in the working area of the Pasar Minggu District Health Center experienced a nutritional status of 73 (79.3%). Pregnant women with sufficient carbohydrate intake were 73 with a percentage (79.3%), pregnant women with sufficient fat intake were 70 with a percentage (76.1%) and pregnant women with sufficient protein intake were 61 with a percentage (66.3%) Based on the Fisher exact statistical test, Statistical relationship between macronutrient intake and nutritional status of pregnant women (p = 0.001) Suggestion: It is hoped that pregnant women can anticipate or prevent poor nutritional status by consuming foods containing carbohydrates, proteins and fats in balance with consultation with health authorities. Health workers should actively provide health information to pregnant women, especially regarding food intake which is important for pregnant women.